Mechanical analysis of asphalt pavement based on bimodulus elasticity theory. (27th September 2021) - Pan, Qinxue; Zheng, Cece; Song, Xiaojin; Lv, Songtao; Yu, Huanan; Zhang, Junhui; Borges Cabrera, Milkos; Liu, Honglin
Highlights: The bimodulus elasticity theory was first introduced into the mechanical analysis of pavement structure. A numerical calculation method of asphalt pavement structure based on bimodulus theory was established. The mechanical response characteristics of asphalt pavement based on bimodulus theory were revealed. Abstract: The bimodulus elasticity theory was introduced into pavement mechanical analysis for the first time in this study. By developing an efficient finite element method of bimodulus structural calculation for asphalt pavement, the mechanical analysis of typical asphalt pavement structure in China was carried out. The results indicated that the mechanical properties of asphalt pavement based on the bimodulus theory are nonlinear and anisotropy. Besides, the deviation between the mechanical response calculation based on bimodulus elasticity theory and the traditional linear case was more than 50%. Moreover, a great deviation on the normal stress and strain was reported, but in the case of the shear stress and shear strain, a small error was found. Especially the mechanical response of the key points in pavement design was greatly affected by the difference in tensile and compressive moduli of surface layer and base cemented mixture, which had its maximum deviation is up to 280%. Due to the significant and inevitable difference in the tensile and compression modulus of pavement materials, the bimodulus elasticity theory is suggested to be used in the mechanical calculation of asphalt pavement design.